Correlation between tidal breathing pulmonary function, exhaled nitric oxide and airway hyperresponsiveness in children aged 0–3 years with suspected asthma - Jiangjiao Qin; Jiangjiao Qin; Fangjun Liu; Fangjun Liu; Ting Wang; Ting Wang; Zhou Fu; Zhou Fu; Ying Lin; Ying Lin; Xia Wang; Xia Wang; et al. (Frontiers in Pediatrics)
ObjectiveTo investigate the correlation between tidal breathing pulmonary function parameters combined with mixed exhaled gas nitric oxide values and the degree of airway hyperresponsiveness (AHR) in children aged 0–3 years with suspected asthma.MethodsIn this retrospective study, we collected baseline clinical data, tidal breathing pulmonary function parameters (measured before methacholine inhalation), fractional exhaled nitric oxide (FeNO) levels, and methacholine challenge test (MCT) results from 818 pediatric asthma patients treated at the Children's Hospital of Chongqing Medical University between January 2021 and June 2023. Baseline data, tidal respiratory pulmonary function parameters, and FeNO values were used to analyze their correlation with AHR. Ordinal multiclass logistic regression analysis was used to identify factors influencing AHR. The receiver operating characteristic (ROC) curve was performed to evaluate the efficacy of predicting AHR using tidal breathing pulmonary function parameters and FeNO values.ResultsIntergroup comparisons showed significant differences in age, weight, height, FeNO, TPTEF/TE, RR, TI/TE, TEF50/TIF50, and PTFE/TEF25 (P < 0.05). Further ordinal multiclass logistic regression analysis revealed that increases in FeNO, RR, and PTEF/TEF25 were significantly positively correlated with AHR severity (P < 0.001), while age was significantly negatively correlated (P < 0.001). FeNO showed reasonable accuracy in predicting AHR at methacholine concentrations of 8 mg/ml (AUC=0.774) and a cut-off value of 14 ppb (sensitivity 88.5%, specificity 63.8%). The combined parameters (FeNO, RR, PTFE/TEF25, and age) showed high accuracy in predicting AHR at methacholine concentrations of 0.5 mg/ml (AUC=0.847).ConclusionsOur study revealed that Current airway inflammation and airway obstruction predicted AHR at this point.FeNO, RR, PTEF/TEF25, and age were effective predictive parameters for the degree of AHR in children aged 0–3 years with suspected asthma; FeNO >14 ppb served as an independent factor suggesting AHR in children at methacholine concentrations of 8 mg/ml, and the combined parameters showed better predictive efficacy.